Evaluación fenológica de cañamo ¿Un cultivo prometedor? - Arizio, Carla Marcela; Fuentes Baluzzi, Virginia; Guariniello, Julian; D' Onofrio, Mariano Sebastian; Mogni, Javier Alejandro; Mazzoni, Ariel Omar; Quintana, Matias; Perez Pizarro, Julián; Paez, Sandra Silvana; Balmaceda, Mariana Andrea; Mieja Andrada, Claudio Nahuel; Garcia, José María; et al. (AAPRESID, 2025)
Poster